Comparison of efficacy of exosomes derived from human umbilical cord blood mesenchymal stem cells in treating mouse acute lung injury via different routes - Chen, Jing; Liu, Shuang; Zou, Jizhen; Wang, Yi; Ge, Haiyan; Hui, Yi; Huang, Siyuan; Li, Wei; Na, Weilan; Huang, Xiaolan; Bai, Lin; Huang, Yiying; et al. (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the therapeutic efficacy of human umbilical cord blood mesenchymal stem cell-derived exosomes (hUCMSC-Exo) in a lipopolysaccharide (LPS)-induced acute lung injury (ALI) mouse model and compare the effects of different administration routes.MethodsAn ALI mouse model was established through intratracheal LPS injection. Mice received hUCMSC-Exo through tail vein injection, nasal drip, or atomization at 4-and-24 h post-modeling, with comparisons made across low, medium, and high doses. Mice were categorized into three groups: control, LPS model, and experimental (n = 8). Histopathological scoring assessed lung inflammation after 48 h; and inflammatory cytokine levels (TNF-α, IL-6, IL-1β, and IL-10) in serum and bronchoalveolar lavage fluid (BALF) were quantified by enzyme-linked immunosorbent assay (ELISA).ResultsIn a murine model of LPS-induced ALI, administration of hUCMSC-Exo via intravenous, intranasal, or nebulized routes at 4 and 24 h post-LPS exposure significantly attenuated pulmonary inflammation, as evidenced by reduced alveolar inflammatory cell infiltration, hemorrhage, and edema in histopathological analysis (except the nebulized low-dose group). ELISA revealed that hUCMSC-Exo markedly decreased serum and bronchoalveolar lavage fluid (BALF) levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β (P < 0.05) while increasing IL-10 levels. Dose-dependent effects were observed across routes: intravenous high-dose (Exo-VH) outperformed medium- and low-dose groups (P < 0.05); intranasal medium-dose (Exo-NM) was superior to low-dose (Exo-NL; P < 0.05), with no significant difference between medium and high doses (P > 0.05); nebulized high-dose (Exo-AH) demonstrated enhanced efficacy over medium- (Exo-AM; P < 0.05) and low-dose (Exo-AL; P < 0.05). At an equivalent dose (5 × 10⁸ particles), intravenous delivery achieved superior lung injury score reduction and cytokine modulation compared to intranasal and nebulized routes (P < 0.05), whereas the latter two showed comparable efficacy (P > 0.05). These findings collectively highlight the therapeutic potential of hUCMSC-Exo in ALI, with intravenous administration emerging as the optimal route at the tested dose.ConclusionhUCMSC-Exo effectively attenuates LPS-induced ALI in mice. At the tested dose (5 × 10⁸ particles), intravenous delivery exhibited superior therapeutic efficacy over intranasal and nebulized routes.